REPRESENTASI BABAD PASANGGRAHAN MADUSITA MENGENAI MODERNITAS DAN HEDONISME PADA AWAL ABAD XX - Adi Putra Surya Wardhana; Dennys Pradita (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2022)
This research aims to analyse the representation of Babad Pasanggrahan Madusita on modernity and hedonism. The hedonist lifestyle of the royal elite was influenced by modernity in the late nineteenth and early twentieth century. During the Paku Buwana X era, Surakarta Hadiningrat Sultanate carried out modernisation. This study used qualitative data analysis methods using the point of view of cultural studies. The research problems are how modernity characterises the lifestyle of hedonism in Babad Pasanggrahan Madusita, the form of representation, and the meaning of Babad Pasanggrahan Madusita. Several previous studies focused on aspects of a manuscript’s locality, moral values, education, culture, and religion. Therefore, this study has arranged to fill the gap in the study of the representation of modernity and hedonism in manuscripts influenced by discourses resulting from the interaction of Javanese culture and European culture. The results showed that Babad Pasanggrahan Madusita was written when modernity became the zeitgeist. At the end of the nineteenth century, hedonism was the lifestyle of the aristocrats, supported by modernisation. The form of Babad Pasanggrahan Madusita was represented by the narrative of the journey and recording of Pesanggrahan Madusita’s assets. The meaning was related to the progress and splendour during the period of Paku Buwana X as the Emperor of Java in the modern era.